(untitled) (Chichester, West Sussex, UK,Ames, Iowa, 2009)
Fishery Products brings together details of all the major methodologies used to assess the quality of fishery products in the widest sense. Subject coverage of this important book includes quality assessment by texture measurement, by electronic nose and tongue, by NMR, and by color measurement. The book also includes several chapters on assessment of authenticity, which is extremely important for the determination of which species have been used in a particular food product containing fish or shellfish
Keywords: Các sản phẩm từ cá,Chế biến cá,Fishery products,Fishery processing; Quản lý chất lượng,Quản lý chất lượng,Quality control,Quality control